Diagnosis and Management of Mirizzi Syndrome Related to Gallstones: A Narrative Literature Review - Diego Lesgenia; Arnelis; Saptino Miro (HM Publisher, 2022)
Mirizzi syndrome (MS) is a rare condition caused by compression of the common hepatic duct due to gallstones located in the cystic duct or neck of the gallbladder. Biliary pain, jaundice, and fever are the most common clinical manifestations of MS. Patients usually report a history of biliary pain with jaundice. There are no pathognomonic features in the history and physical examination. Patients may also come with acute cholecystitis, acute cholangitis, or pancreatitis. In cases where MS is suspected, the diagnosis can be made by ultrasonography (US), computed tomography (CT), magnetic resonance cholangiopancreatography (MRCP), and endoscopic retrograde cholangiopancreatography (ERCP). Surgery is the main treatment for cases of MS and is a challenge because preoperative diagnosis is difficult, thus impacting management during surgery. This literature review aimed to describe the features of MS related to gallstones and management options.